2016
DOI: 10.1128/iai.00447-16
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic di-AMP Released from Staphylococcus aureus Biofilm Induces a Macrophage Type I Interferon Response

Abstract: Staphylococcus aureus is a leading cause of community-and nosocomial-acquired infections, with a propensity for biofilm formation. S. aureus biofilms actively skew the host immune response toward an anti-inflammatory state; however, the biofilm effector molecules and the mechanism(s) of action responsible for this phenomenon remain to be fully defined. The essential bacterial second messenger cyclic diadenylate monophosphate (c-di-AMP) is an emerging pathogen-associated molecular pattern during intracellular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 65 publications
3
49
0
1
Order By: Relevance
“…Due to the absence of PSMs, which would otherwise disperse biofilm-like aggregates, this leads to pronounced clumping and increased resistance to antibiotic treatment. Finally, recent research suggests that S. aureus biofilms release specific factors, such as cyclic di-AMP, that limit inflammation (Gries et al, 2016). Thus, biofilm formation on indwelling medical devices can be seen as a strategy to evade elimination by the immune system by remaining in a relatively quiescent state that does not trigger pronounced inflammation, in addition to providing increased shelter from phagocyte attacks and antibiotics.…”
Section: Biofilm Formation As An Immune Evasion Strategymentioning
confidence: 99%
“…Due to the absence of PSMs, which would otherwise disperse biofilm-like aggregates, this leads to pronounced clumping and increased resistance to antibiotic treatment. Finally, recent research suggests that S. aureus biofilms release specific factors, such as cyclic di-AMP, that limit inflammation (Gries et al, 2016). Thus, biofilm formation on indwelling medical devices can be seen as a strategy to evade elimination by the immune system by remaining in a relatively quiescent state that does not trigger pronounced inflammation, in addition to providing increased shelter from phagocyte attacks and antibiotics.…”
Section: Biofilm Formation As An Immune Evasion Strategymentioning
confidence: 99%
“…Increased expression of CDNs promotes extracellular matrix production and biofilm formation . CDNs released from bacterial biofilm can also activate host immune responses . Previous studies showed that CDNs could be used as novel vaccine adjuvants or immunostimulatory molecules for host defense .…”
Section: Introductionmentioning
confidence: 99%
“…(15)(16)(17) CDNs released from bacterial biofilm can also activate host immune responses. (18) Previous studies showed that CDNs could be used as novel vaccine adjuvants or immunostimulatory molecules for host defense. (19)(20)(21)(22) Intranasal administration with c-di-GMP enhances bacteria clearance and protects mice from Klebsiella pneumoniae infection through stimulation of dendritic cell-meditated responses.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, STING was shown to be a direct sensor of c-di-GMP (Burdette et al, 2011). Since then, studies have shown that STING mediates a type I IFN response specifically in response to CDNs such as those produced by Staphylococcus aureus and Chlamydia trachomatis (Barker et al, 2013; Gries et al, 2016; Zhang et al, 2014). Undoubtedly, the role of STING in detecting CDN-mediated type I IFN response was authenticated by the discovery that cGAS produces cGAMP in a DNA-dependent manner (Sun et al, 2013).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%